The developing immune network in human prenatal skin. Issue 2 (14th April 2020) - Botting, Rachel Anne; Haniffa, Muzlifah
Summary: Establishment of a well‐functioning immune network in skin is crucial for its barrier function. This begins in utero alongside the structural differentiation and maturation of skin, and continues to expand and diversify across the human lifespan. The microenvironment of the developing human skin supports immune cell differentiation and has an overall anti‐inflammatory profile. Immunologically inert and skewed immune populations found in developing human skin promote wound healing, and as such may play a crucial role in the structural changes occurring during skin development. Abstract : The immune system in skin is established early during development. Throughout development it continues to expand and diversify.